Exploring the Role of Technology-Assisted Language Learning in Facilitating Oral Fluency Development in EFL Classrooms The Case Study of 3rd year EFL Students at Souk Ahras University. - Yasmine BELGUIDOUM (My University, 2025)
Abstract This study investigates the impact of Technology-Assisted Language Learning (TALL) on the development of oral fluency among third-year EFL students at Mohamed Cherif Messaadia University, Souk Ahras. Oral fluency, which includes the smooth and accurate use of language, remains a major challenge for many learners due to factors such as limited vocabulary, pronunciation difficulties, and a lack of coherence and speed during speaking tasks. This research aims to explore the extent to which TALL tools such as speech recognition applications, online platforms, video-based learning platforms, and classroom tools can support the improvement of these oral fluency components. The study adopts a descriptive and exploratory research design, using both quantitative and qualitative methods to gather and interpret data. An online structured questionnaire was distributed to a sample of 45 third-year EFL students, with the aim of collecting their perceptions, practices, and experiences related to the use of TALL tools. The findings reveal that the majority of participants use digital tools regularly to improve their oral fluency and report significant benefits, particularly in pronunciation, vocabulary acquisition, coherence, and speech pace. Furthermore, students perceive TALL tools as accessible, motivating, and helpful in increasing their confidence and autonomy. These results suggest that integrating technology-based methods in speaking instruction can enhance oral fluency and support learners' engagement in real-world communication. The dissertation concludes with pedagogical recommendations for both teachers and learners to make the most of TALL tools in the language classroom. ----------------------- الملخص يتناول هذا البحث تأثير التعلم المدعوم بالتكنولوجيا TALL على تطوير الطلاقة الشفوية لدى طلاب السنة الثالثة في قسم اللغة الإنجليزية كلغة أجنبية بجامعة محمد الشريف مساعدية في سوق أهراس. تمثل الطلاقة في الحديث تحديًا شائعًا للمتعلمين بسبب مشاكل مثل ضعف النطق، قلة المفردات، غياب الترابط في الكلام، وانخفاض مستوى الثقة بالنفس. يهدف هذا البحث إلى معرفة مدى مساهمة الأدوات التكنولوجية مثل تطبيقات التعرف على الصوت، المنصات الإلكترونية، ومنصات التعلم المرئي، في تحسين هذه الجوانب. اعتمدت الدراسة على تصميم وصفي واستكشافي، واستخدمت أسلوبًا يجمع بين البيانات الكمية والنوعية. تم توزيع استبيان إلكتروني على عينة قصدية مكونة من 45 طالبًا لاستكشاف آرائهم وتجاربهم في استخدام أدوات TALL. كشفت النتائج أن معظم الطلاب يستخدمون هذه الأدوات بانتظام ويلاحظون تحسنًا في النطق، وزيادة في المفردات، وتطورًا في سرعة الحديث. كما اعتبر الطلاب هذه الأدوات مشجعة وسهلة الاستخدام وتساهم في رفع ثقتهم بأنفسهم أثناء الحديث. تشير النتائج إلى أن دمج التكنولوجيا في تعليم مهارات التحدث يمكن أن يساعد في تحسين الطلاقة الشفوية وزيادة تفاعل الطلاب داخل القسم وخارجه. ------------------------ Resumé Cette recherche explore comment l'apprentissage des langues assisté par la technologie (TALL) soutiennent les étudiants en troisième année d'anglais langue étrangère à l'Université Mohamed Cherif Messaadia de Souk Ahras à perfectionner leur aisance verbale. Les défis examinés comprennent des problèmes de prononciation, une insuffisance de vocabulaire et des complications à structurer leurs pensées de façon logique. Un questionnaire a été soumis à 45 étudiants. Les réactions indiquent que la majorité d'entre eux trouvent ces dispositifs technologiques bénéfiques, surtout pour améliorer leur prononciation, développer leur fluidité verbale et renforcer leur confiance lors de prises de parole. Selon la conclusion de l'étude, les outils TALL utilisés dans ce contexte particulier montrent une corrélation positive avec le développement ciblé des compétences orales. Ces observations indiquent que l'incorporation de technologies éducatives pourrait enrichir les approches traditionnelles dans les cursus d'enseignement des langues, à condition de surmonter certaines contraintes techniques détectées.
Keywords: Technology-Assisted Language Learning; oral fluency; EFL students; pronunciation; vocabulary; speaking skills; digital tools; classroom integration; التعلم المدعوم بالتكنولوجيا، الطلاقة الشفوية، طلاب اللغة الإنجليزية، النطق، المفردات، الأدوات الرقمية، مهارات التحدث.; Apprentissage des langues assisté par la technologie (TALL); fluidité orale; apprenants d'anglais langue étrangère; prononciation; vocabulaire; cohérence; compétences orales; technologie éducative.